The long-term growth impact of refugee migration in Europe: A case study - Gerrit Manthei (Albert-Ludwigs-Universität Freiburg, Forschungszentrum Generationenverträge (FZG), 2020)
Many questions have been raised about the political and economic consequences of the recent surge in refugee immigration in Europe. Can refugee immigration promote long-term per-capita growth? How are the drivers of per-capita growthinfluenced by immigration? What are the policy implications of refugee immigration? Using an adjusted Cobb-Douglas productionfunction,with labour divided into two complementary groups,this study attempts to provide some answers. By applying the model to current immigration data from Germany, the study finds that refugee immigration can lead to long-term per-capita growth in the host country and that the growth is higher if immigrants are relatively young and have sufficiently high qualifications. Further, capital inflowsare a prerequisite for boosting per-capita growth. These findings can inform the migration policiesof countries that continue to grapple with refugee immigration.
Keywords: E20; F22; O41; 330; Refugee; Immigration; Growth; Labour Supply; Wages